2010
DOI: 10.1111/j.1365-3113.2010.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemerodromiinae (Diptera: Empididae): a tentative phylogeny and biogeographical discussion

Abstract: A cladistic analysis of adult morphological characters was used to hypothesize phylogenetic and zoogeographical relationships in Hemerodromiinae (Diptera: Empididae)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…This subfamily includes the tribes Hemerodromiini and Chelipodini previously assigned to Hemerodromiinae. The genera Afrodromia and Drymodromia were removed from Chelipodini by Plant () and placed incertae sedis within Hemerodromiinae. Following our analysis these two taxa are now unplaced within the subfamily Empidinae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This subfamily includes the tribes Hemerodromiini and Chelipodini previously assigned to Hemerodromiinae. The genera Afrodromia and Drymodromia were removed from Chelipodini by Plant () and placed incertae sedis within Hemerodromiinae. Following our analysis these two taxa are now unplaced within the subfamily Empidinae.…”
Section: Discussionmentioning
confidence: 99%
“…Plant () indicated that the genus Chelipodozus belongs to Hemerodromiini, but with low support. It is herein still considered belonging to Chelipodini until evidence about its relationship is revealed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the dipteran family Empididae, the ‘ Chelipoda ‐like group’ is confined to New Zealand, Lord Howe Island, and New Caledonia (all on continental crust that rifted from Gondwana in the late Cretaceous) and Vanuatu (part of the island arc that rifted from Gondwana in the late Cretaceous. Plant (, p. 83) proposed that the group is ‘a relictual Gondwanan element that has survived Oligocene drowning as metapopulations persisting in situ on ephemeral islands along arcs, ridges and buoyant crustal blocks...’. Likewise, in ambrosia beetles, members of the weevil family Curculionidae, New Caledonian elements: ‘…may have survived as metapopulations on ephemeral islands over tens of millions of years… ’.…”
Section: Metapopulations and Their Survival In Situ By Normal Dispersalmentioning
confidence: 99%
“…In these areas, species from the Brachystomatidae subfamily Ceratomerinae inhabit a similar ecological niche occupied by Wiedemannia in other regions (Sinclair, , , ). Dispersal to South Asia and thereafter Australia might also have been constrained by drying of the continent during the late Miocene, which has been considered the case in Hemerodromiinae (Plant, ).…”
Section: Discussionmentioning
confidence: 99%